2021
DOI: 10.1002/ejhf.2092
|View full text |Cite
|
Sign up to set email alerts
|

Oral sucrosomial iron improves exercise capacity and quality of life in heart failure with reduced ejection fraction and iron deficiency: a non‐randomized, open‐label, proof‐of‐concept study

Abstract: Aims Oral sucrosomial iron (SI) combines enhanced bioavailability and tolerance compared to conventional oral iron along with similar efficacy compared to intravenous iron in several conditions associated with iron deficiency (ID). Methods and results In this non‐randomized, open‐label study, we sought to evaluate prospectively the effects of SI on clinical parameters, exercise capacity and quality of life in 25 patients with heart failure (HF) with reduced ejection fraction (HFrEF) and ID, treated with SI 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…59 In a recently published study, however, oral sucrosomial iron was associated with improved exercise capacity and quality of life in patients with HFrEF and ID; however, only 25 patients were included in this trial, which was open-label and not randomized. 60 The current body of evidence, as described above, supports the use of i.v. iron to treat ID (serum ferritin <100 ng/ml, or ferritin between 100 and 300 ng/ml and TSAT <20%) in HF with HFrEF regardless of the presence or absence of anemia, in order to improve functional status and quality of life.…”
Section: Correcting Anemia or Iron Deficiency In Hfmentioning
confidence: 75%
“…59 In a recently published study, however, oral sucrosomial iron was associated with improved exercise capacity and quality of life in patients with HFrEF and ID; however, only 25 patients were included in this trial, which was open-label and not randomized. 60 The current body of evidence, as described above, supports the use of i.v. iron to treat ID (serum ferritin <100 ng/ml, or ferritin between 100 and 300 ng/ml and TSAT <20%) in HF with HFrEF regardless of the presence or absence of anemia, in order to improve functional status and quality of life.…”
Section: Correcting Anemia or Iron Deficiency In Hfmentioning
confidence: 75%
“…Iron deficiency is a major therapeutic target in HF 9,14,22 . In a non‐randomized, open‐label, prospective pilot study, oral sucrosomial iron improved exercise capacity and QoL in patients with HFrEF and Iron deficiency, with significant improvement in 6‐min walk distance and KCCQ at 3 and 6 months (all adjusted P ‐values <0.01) 23 …”
Section: Treatment Of Heart Failure With Reduced Ejection Fractionmentioning
confidence: 97%
“…9,14,22 In a nonrandomized, open-label, prospective pilot study, oral sucrosomial iron improved exercise capacity and QoL in patients with HFrEF and Iron deficiency, with significant improvement in 6-min walk distance and KCCQ at 3 and 6 months (all adjusted P-values <0.01). 23 stromal cells (MSCs) in patients with ischaemic HF. 24 The Phase II CONCERT-HF trial demonstrated that the combination of MSCs and c-kit positive cardiac cells was associated with further improvement in clinical outcome and QoL.…”
Section: Iron Deficiencymentioning
confidence: 99%
“…In this issue of the Journal, Karavidas et al 14 . report, for the first time, the results of a non‐randomized, single‐centre, uncontrolled, open‐label study of the effects of SI in HFrEF.…”
Section: Figurementioning
confidence: 99%
“…In an open-label randomized trial in renal patients, SI was well tolerated and as effective as IV ferrous gluconate in correcting anaemia. 13 In this issue of the Journal, Karavidas et al 14 report, for the first time, the results of a non-randomized, single-centre, uncontrolled, open-label study of the effects of SI in HFrEF. They enrolled 50 patients with symptomatic chronic HFrEF, a left ventricular ejection fraction <40%, and ID as defined by the FERRIC-HF criteria (ferritin <100 μg/L or ferritin 100-300 μg/L with transferrin saturation <20%).…”
mentioning
confidence: 99%